A little can go a long way: giving learners some context can enhance the benefits of pretesting. Issue 9 (21st October 2021) - Overoye, Acacia L.; James, Kelsey K.; Storm, Benjamin C.
ABSTRACT: Tests given to learners before they study new information can enhance the learning of that information. When responding to these pretests, learners typically generate answers that are incorrect but that are nevertheless helpful for improving the learning of the correct answers. The present research examined how providing learners with context prior to pretesting can enhance the benefits of pretesting. Across two experiments, participants were given a pretest for half of the to-be-learned information and then asked to read a passage about a fictional topic, an alien civilisation known as Yoffas (Experiment 1 and Experiment 2), or a unique fruit called the Anona (Experiment 2). Participants who read a short paragraph contextualising the to-be-learned information exhibited a significantly larger pretesting effect than participants who did not, with this interaction being observed regardless of whether memory was tested after a 5-min delay or 1-week delay, and regardless of whether contextualisation was manipulated between-subjects or within-subjects. These results suggest that what learners know prior to a pretest can have an impact on the extent to which learners benefit from that pretest.